2012
DOI: 10.1186/1750-1326-7-21
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MMP-9 by a selective gelatinase inhibitor protects neurovasculature from embolic focal cerebral ischemia

Abstract: BackgroundCerebral ischemia has been shown to induce activation of matrix metalloproteinases (MMPs), particularly MMP-9, which is associated with impairment of the neurovasculature, resulting in blood–brain barrier breakdown, hemorrhage and neurodegeneration. We previously reported that the thiirane inhibitor SB-3CT, which is selective for gelatinases (MMP-2 and −9), could antagonize neuronal apoptosis after transient focal cerebral ischemia.ResultsHere, we used a fibrin-rich clot to occlude the middle cerebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
110
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 47 publications
8
110
0
Order By: Relevance
“…In fact, SB-3CT-treatment for 7 days in a permanent mouse model of ischemia is neuroprotective. 15 NXY-059, a free radical trapping agent that failed in clinical trials for acute ischemic stroke, has been reported to lack BBB penetration. 16 Recently, NXY-059 was shown to have limited brain penetration with maximal brain concentrations of 6 pmol/mg (equivalent to approximately 1% of plasma concentration) after continuous intravenous infusion to rats at 125 mg/kg.…”
mentioning
confidence: 99%
“…In fact, SB-3CT-treatment for 7 days in a permanent mouse model of ischemia is neuroprotective. 15 NXY-059, a free radical trapping agent that failed in clinical trials for acute ischemic stroke, has been reported to lack BBB penetration. 16 Recently, NXY-059 was shown to have limited brain penetration with maximal brain concentrations of 6 pmol/mg (equivalent to approximately 1% of plasma concentration) after continuous intravenous infusion to rats at 125 mg/kg.…”
mentioning
confidence: 99%
“…Nevertheless, we observed that MMP-9 was the predominant gelatinase under our experimental conditions. 8,20,21,32 It should be noted, however, that our present ACPPs do not discriminate between MMP-2 and MMP-9, although we are actively developing more selective ACPPs.…”
Section: Discussionmentioning
confidence: 99%
“…Two mouse models of focal cerebral ischemia were used in this study: a filament-occlusion model and an embolic ischemia model, representing mechanical blockage and clot-induced occlusion, respectively, as we have previously described. 20,21 All animal experiments were approved by the University of Missouri-Columbia Animal Care and Usage Committee and performed in accordance with the ARRIVE guidelines. Adult male C57BL/6J mice (8-10 weeks old from The Jackson Laboratory, Bar Harbor, ME), weighing 20-25 g, were housed in a 12-h light/dark cycle and permitted food and water intake ad libitum.…”
Section: Experimental Models Of Focal Cerebral Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Latronico and Liuzzi as the ability to prevent damage during cerebral ischemia 27 and to attenuate damage resulting from traumatic brain injury. 28 An attempt to develop specific inhibitors of MMP-2 and MMP-9 was made by synthesizing cyclic peptides corresponding to the frequently observed motifs in MMPactive sites, thus preventing substrate access.…”
mentioning
confidence: 99%